2020
DOI: 10.1210/clinem/dgaa856
|View full text |Cite
|
Sign up to set email alerts
|

Role of Imprinting Disorders in Short Children Born SGA and Silver-Russell Syndrome Spectrum

Abstract: Background (Epi)genetic disorders associated with small-for-gestational-age with short stature (SGA-SS) include imprinting disorders (IDs). Silver-Russell syndrome (SRS) is a representative ID in SGA-SS and has heterogenous (epi)genetic causes. Subjects and Methods To clarify the contribution of IDs to SGA-SS and the molecular and phenotypic spectrum of SRS, we recruited 269 patients with SGA-SS consisting of 103 and 166 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…We identified two rare cases with severe prenatal and postnatal growth failure together with some SRS features caused by microdeletions involving the KCNQ1OT1 :TSS-DMR on the paternal allele which leads to CDKN1C hyperexpression, and conducted detailed clinical and genetic analyses in the patients and their family members. Clinical manifestations of patients 1 and 2 were similar to those of patients with H19 LOM, UPD(7)mat17 or CDKN1C GOF variant4–7 (table 1). Notably, both patients showed poor responses to GH treatment.…”
Section: Discussionsupporting
confidence: 55%
“…We identified two rare cases with severe prenatal and postnatal growth failure together with some SRS features caused by microdeletions involving the KCNQ1OT1 :TSS-DMR on the paternal allele which leads to CDKN1C hyperexpression, and conducted detailed clinical and genetic analyses in the patients and their family members. Clinical manifestations of patients 1 and 2 were similar to those of patients with H19 LOM, UPD(7)mat17 or CDKN1C GOF variant4–7 (table 1). Notably, both patients showed poor responses to GH treatment.…”
Section: Discussionsupporting
confidence: 55%
“…The diagnostic yield of NGS in SGA in the present study was 21 (24.1%) of 87, among whom 13 (14.9%) and 8 (9.2%) had P/LP variants in genes and CNVs which was below that of the total cohort (361/814; 44.3%) ( P < .05). Imprinted genes in the placenta are important for the control of fetal growth ( 34 , 35 ). A recent study of 269 patients with SGA with short stature reported a diagnostic yield of 107 (39.78%) of the 269 patients by comparative genomic hybridization combined with methylation analysis, and 32.34% (87/269) patients were diagnosed with imprinting disorders and 7.44% (20/269) were CNVs ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Imprinted genes in the placenta are important for the control of fetal growth ( 34 , 35 ). A recent study of 269 patients with SGA with short stature reported a diagnostic yield of 107 (39.78%) of the 269 patients by comparative genomic hybridization combined with methylation analysis, and 32.34% (87/269) patients were diagnosed with imprinting disorders and 7.44% (20/269) were CNVs ( 35 ). The diagnostic power of exome sequencing in SGA is limited; further methylation analysis can be an effective approach to diagnose SGA, and environmental causes for SGA should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…We enrolled 130 patients with aneuploid UPD-IDs con rmed by molecular studies, including 77 previously reported patients (UPDmat of chromosome 7 (n = 9) [20], UPD( 14)pat (n = 19) [21], UPD( 14)mat (n = 17) [22], UPD( 15)mat (n = 27) [17], and UPDmat of chromosome 20 (n = 5) [23]). We classi ed these 130 patients into UPD-IDs caused by aneuploid oocytes or sperms based on the UPD subtypes con rmed by microsatellite analysis and SNP array analysis.…”
Section: Patientsmentioning
confidence: 99%